Unexpectedly low δ 13C in leaves, branches, stems and roots of three acacia species growing in hyper-arid environments. (21st November 2020) - Uni, Daphna; Groner, Elli; Soloway, Elaine; Hjazin, Amgad; Johnswick, Spencer; Winters, Gidon; Sheffer, Efrat; Rog, Ido; Wagner, Yael; Klein, Tamir
Abstract: Aims: In plant eco-physiology, less negative (enriched) carbon 13 ( 13 C) in the leaves indicates conditions of reducing leaf gas exchange through stomata, e.g. under drought. In addition, 13 C is expected to be less negative in non-photosynthetic tissues as compared with leaves. However, these relationships in δ 13 C from leaves (photosynthetic organs) to branches, stems and roots (non-photosynthetic organs) are rarely tested across multiple closely related tree species, multiple compartments, or in trees growing under extreme heat and drought. Methods: We measured leaf-to-root 13 C in three closely related desert acacia species ( Acacia tortilis, A. raddiana and A. pachyceras ). We measured δ 13 C in leaf tissues from mature trees in southern Israel. In parallel, a 7-year irrigation experiment with 0.5, 1.0 or 4.0 L day −1 was conducted in an experimental orchard. At the end of the experiment, growth parameters and δ 13 C were measured in leaves, branches, stems and roots. Important Findings: The δ 13 C in leaf tissues sampled from mature trees was ca. −27‰, far more depleted than expected from a desert tree growing in one of the Earth's driest and hottest environments. Across acacia species and compartments, δ 13 C was not enriched at all irrigation levels (−28‰ to ca. −27‰), confirming our measurements in the mature trees. Among compartments, leaf δ 13 C was unexpectedly similar to branch and root δ 13 C, and surprisingly, even less negative than stem δ 13 C. The highly depleted leaf δ 13 C suggests that these trees have high stomatal gas exchange, despite growing in extremely dry habitats. The lack of δ 13 C enrichment in non-photosynthetic tissues might be related to the seasonal coupling of growth of leaves and heterotrophic tissues.